Patronimy jako składniki osobowego kodu identyfikacyjnego Żydów poznańskich od XVI do XVIII wieku - Sarnowska-Giefing, Irena (Poznańskie Spotkania Językoznawcze, 2015)
The subject of this article are patronymic surnames of the Poznań Jews used during the period from the 16th to the 18th century. According to the author of the article nonderivative patronymic names, formed according to the model given name + one’s father’s given name, were dominant in the given period. They were based on the German anthroponomastic system. This model was definitely imposed on the Jews in the whole area of the Prussian Partition under a Decree issued in 1797 by king Frederick William II. Under the Decree the Jews were made tax liable and were obliged to have hereditary surnames. The author of the article proves that until the end of the 18th century patronimic personal names were based directly on the given name of one’s father (in every generation), so they were not family surnames. The author also describes other types of patronymic personal names of Jews well-documented in historical sources of Poznań.